Leishmaniose mucosa: marcadores clínicos no diagnóstico presuntivo - Joao Luiz Cioglia Pereira Diniz (2010)
Mucocutaneous Leishmaniasis (ML) can leave serious sequelae and stigma. Early diagnosis prevents complications. Objective: To evaluate the clinical markers used for the diagnosis of ML. Methods: Twenty one patients from the metropolitan region of Belo Horizonte with confirmed diagnosis of ML were evaluated through clinical interview, nasal endoscopy and biopsy, Montenegro skin test. Results: The mean age was 59 years, seven (35%) and 14 women (65%) men. Typical cutaneous scar or previous history of cutaneous leishmaniasis were observed in eight patients (38%) and 13 (62%) denied history of leishmaniasis and had no scar. The onset of nasal or oral symptoms until the definition of diagnosis ranged from five to 240 months, an average of 65,48 months. In Montenegro skin test, the average size of papule was 14,5 mm and size did not correlate with the duration of the disease (p = 0.87). Nasal involvement predominated and extension of the lesion in mucosa did not correlate with the duration of the disease. Parasites were found in two (9.52%) specimens of lesions submitted to biopsy. Conclusion: in the evaluated geographical area, diagnosis of the ML was late. Skin scars and cutaneous leishmaniasis prior history were not good clinical markers for diagnosing ML. Otolaryngologic evaluation, Montenegro skin test and histopathologic examination of injuries in the mucosa for exclusion of other diseases remain important markers for the diagnosis of ML.